2014
DOI: 10.1111/jocd.12104
|View full text |Cite
|
Sign up to set email alerts
|

Women's perceptions of the benefits and risks of skin‐lightening creams in two South African communities

Abstract: Skin-lightening products are used by a third of African and Indian women in South Africa Cultural and historical perceptions equating a fairer skin with social advantage are pervasive and strongly reinforced by the media. There is a poor understanding of the risks associated with the use of these products. Public education campaigns are required to teach consumers about these risks and the importance of concomitant use of sunscreens with these products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 16 publications
9
52
1
2
Order By: Relevance
“…Cette pratique est répandue en Afrique sub-saharienne, où elle a été décrite pour la première fois en Afrique du Sud et au Sénégal [1]. En Afrique du Sud, la DV est pratiquée aussi bien par la population noire que par la population indienne, et la plupart des utilisatrices des produits dépigmentants sont conscientes de ses effets secondaires [2]. Une étude menée à Dakar a montré que la pratique de la DV concernait près de 67 % de la population féminine, avec comme impact un poids économique estimé à 19 % des revenus des utilisatrices [3].…”
unclassified
“…Cette pratique est répandue en Afrique sub-saharienne, où elle a été décrite pour la première fois en Afrique du Sud et au Sénégal [1]. En Afrique du Sud, la DV est pratiquée aussi bien par la population noire que par la population indienne, et la plupart des utilisatrices des produits dépigmentants sont conscientes de ses effets secondaires [2]. Une étude menée à Dakar a montré que la pratique de la DV concernait près de 67 % de la population féminine, avec comme impact un poids économique estimé à 19 % des revenus des utilisatrices [3].…”
unclassified
“…A more European or Asian looking hairstyle is also preferable to natural African hair. These tendencies have real-life implications for young women, one being the trend of skin bleaching (Dlova et al 2014). Many women in South Africa fall prey to media-portrayed images of "thinness equals beauty" (Szabo & Allwood 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered acceptable for young women to have idols as they grow up and to mould their identity in line with their celebrity idols (Sutton 2009). Studies by, amongst others, Dlova et al (2014) and Sastre (2014), have shown the impact of celebrity culture on various perceptions of elements of beauty. Dlova et al's (2014) study of skin bleaching amongst black women in South Africa shows that out of 292 Africans and 287 Indians included in the survey sample, 32.3% had used skinlightening products (60% of Africans and 40% of Indians).…”
Section: Celebrity Culture and Social Media Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, the global media industry fuelled the notion that fair-skinned people were beautiful and thus, a standard was set for beauty. 11,12 These factors together with trauma of colonization, slavery, discrimination, mistreatment, and colour rating in social class against dark skin continued to be further embedded in the psyche of those with more pigmented skin. In his book, Black skin, white masks , 13 Franz Fanon draws on his own experiences as a black person in a white dominated world.…”
Section: History Of Skin Lightenersmentioning
confidence: 99%